155 Patient support program for RRMS patients treated with DMF. Issue 12 (14th November 2019) - Monterroso, Joana; Curlis, Janette; Gribben, Leontia
Abstract : Introduction: In the UK, the number of patients with relapsing-remitting multiple sclerosis (RRMS) far exceeds the capacity of MS specialist nurses (MSSNs). Methods: Biogen and IQVIA developed a remote, nurse-led, script-based telephone line to provide educational assistance and support treatment adherence among adult RRMS patients receiving delayed-release dimethyl fumarate (DMF). In the year following DMF initiation, 8 calls are scheduled over the first 3 months, followed by 3 quarterly calls. An optional online satisfaction survey was added to the program in July 2017. Results: Based on summarized call data from March 2015 through November 2018, 1204 patients were enrolled from 136 UK hospitals, with a mean (median, range) of 8.5 (2, 1–168) patients/hospital. An average of 10.8 calls/patient were received. Across 11 scheduled calls, average time/call was 13 minutes. Over this period, cumulative reported DMF discontinuation among enrolled patients was 12.7%. Between July 2017 and September 2018, 76% of survey responders treated for ≥1 year (n=78) would recommend the service (score ≥5, scale: 1 [not at all] to 7 [extremely likely]). Conclusion: This program has been widely used and positively received across the UK by DMF-treated patients and should help reduce the burden on MSSNs. Support: Biogen. Disclosures to be presented on poster.